2013
DOI: 10.1074/jbc.m113.468629
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Hyaluronan Enhances Innate Defense of the Intestinal Epithelium

Abstract: Background: Human milk contains hyaluronan (HA).Results: Milk HA concentration is highest immediately after delivery. Treatment of epithelium with physiologic levels of milk-derived HA increases intracellular expression of ␤-defensin (in vitro and in vivo) and resistance to Salmonella. Conclusion: Milk HA enhances functional antimicrobial defense mechanisms of the intestinal epithelium. Significance: Milk HA may be a mediator of maternal protection of newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 81 publications
1
82
0
Order By: Relevance
“…In addition to the epithelial tight junctions, the mucus contributes to the overall barrier function of the epithelia. The tion expands HA's proposed role in protection of mucosal epithelia, as a recent study reported the importance of HA in breast milk to activate antimicrobial expression in gut mucosal epithelia of the offspring ingesting the milk (25). The fact that vaginal HA application from d12 to d17 failed to rescue the sensitivity to PTB in Has1/2/3 KO mice, as well as the failed restoration of permeability in HA-treated ECT-1 cells with siRNA-mediated Has3 knockdown, suggest that HA function is more complex than simply improving the barrier properties of the mucus.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to the epithelial tight junctions, the mucus contributes to the overall barrier function of the epithelia. The tion expands HA's proposed role in protection of mucosal epithelia, as a recent study reported the importance of HA in breast milk to activate antimicrobial expression in gut mucosal epithelia of the offspring ingesting the milk (25). The fact that vaginal HA application from d12 to d17 failed to rescue the sensitivity to PTB in Has1/2/3 KO mice, as well as the failed restoration of permeability in HA-treated ECT-1 cells with siRNA-mediated Has3 knockdown, suggest that HA function is more complex than simply improving the barrier properties of the mucus.…”
Section: Discussionmentioning
confidence: 83%
“…Breakdown and turnover of HA occur both at steady state and upon injury. This breakdown is important because high molecular mass HA (HMM-HA) has distinct functions from low molecular mass HA (LMM-HA) (13)(14)(15). LMM-HA (Ͻ75 kDa) can be generated by hyaluronidase-mediated degradation or by tissue injury (16).…”
mentioning
confidence: 99%
“…92 High-molecular-weight hyaluronan isolated from human milk has been demonstrated to enhance antimicrobial peptide expression in intestinal epithelium in vivo through a mechanism dependent on CD44 receptor and Toll-like receptor 4 and to enhance functional resistance of cultured epithelium to enteric infection. 93 Intraperitoneal injection of hyaluronan suppresses immune activation in a murine model of colitis 94 and may also promote the proliferation of antiinflammatory IL-10-secreting T-regulatory cells. 95 Numerous clinical studies have demonstrated the effectiveness of glycosaminoglycan preparations in enhancing wound healing, 96 and glycosaminoglycans may function similarly to enhance GI wound healing.…”
Section: Anti-inflammatory Glycosaminoglycansmentioning
confidence: 99%